Interactive Advertising: Patterns of Use and Effectiveness - Risden, Kristen; Czerwinski, Mary; Worley, Stephanie; Hamilton, Lynda; Kubiniec, Joe; Hoffman, Hunter; Mickel, Nancy; Loftus, Elizabeth (Association for Computing Machinery, Inc., 1998)
The number of people exploring the World Wide Web is growing dramatically. Many companies are interested in the potential of advertising on the Web, but there is little research to guide their decision. The present study demonstrates the concept of a corporate sponsored Web site as a promising direction for Web advertisers. Advertisements for products targeting 10-14 year-olds were presented as Web games and inserted into a prototype Web site. For example, in one ad, players scored points by actively steering toward the advertised product with their Web video-game car, while dodging undesirable obstacles on the road (sound effects included). For comparison, subjects also watched a TV ad for the same product embedded in a TV program. One day later, tests showed that Web ads positively influenced how easily the advertised brand came to mind compared to TV ads and compared to no-ad controls. The effectiveness of interactive Web ads for influencing consumers' memory in this preliminary study suggests that it merits more attention as a potentially viable medium for advertising. Factors that could contribute to the advantage for Web ads are discussed.